Peran Brand Awareness dalam Memediasi Pengaruh Digital Marketing terhadap Kinerja UMKM di Kota Kupang - Alya Elita Sjioen; Angela Merici Minggu; Herry Aprilia Manubulu; Gabriela E. Hetharia; Christian Daniel Manu; Ardi B. T. Ndaumanu (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
This study aims to analyze the role of Brand awareness in mediating the effect of Digital marketing on SME Performance in Kupang City. This research is important because many SMEs still face challenges in optimizing digital marketing strategies and strengthening brand awareness in the rapidly growing digital economy. The novelty of this study lies in the use of Brand awareness as a mediating variable in explaining the relationship between Digital marketing and SME Performance within the context of SMEs in Eastern Indonesia, particularly in Kupang City. This study employed a quantitative approach using a survey method through questionnaires distributed to SMEs actively utilizing digital media in their business activities. The sampling technique used purposive sampling, and data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings indicate that Digital marketing positively and significantly affects Brand awareness and SME Performance. Furthermore, Brand awareness positively influences SME Performance and significantly mediates the relationship between Digital marketing and SME Performance. These results highlight the importance of integrating digital marketing strategies with consistent branding activities to improve competitiveness and business sustainability among SMEs in the digital era.